Enhancing Students' Critical Thinking Skills on the Alternative Energy Topic in Junior High School Through Integrated STEM-PjBL Model - Julia Nur Aini; Heni Rusnayati; Ida Kaniawati (Jurnal Penelitian Pembelajaran Fisika, 2025)
Critical thinking ability is a fundamental ability that every graduate must have in order to be able to adapt to technological and social changes in the 21st century. The aim of this research is to determine the increase in students' critical thinking abilities after learning using the STEM (Science, Engineering, Technology and Mathematics) integrated Project Based Learning learning model. The method used was pre-experiment with a one-group pretest-posttest design. The sample for this research was 30 class VIII students in one of the Bandung City Middle Schools. The sampling technique was carried out using a purposive sampling technique. The instruments used were critical thinking ability tests, student worksheets, student response questionnaires and learning implementation observation sheets. Increased critical thinking was analyzed using N-Gain with an N-Gain value of 0.6306 in the medium category, and students' responses to learning showed positive results. From these results, it was found that the application of the STEM (Science, Technology, Engineering and Mathematics) integrated Project Based Learning learning model can improve students' critical thinking abilities. Based on the results of the discussion, the implications of learning using the Project Based Learning model integrated with STEM (Science, Technology, Engineering and Mathematics) have a significant influence on students' critical thinking skills.